Outcome of Percutaneous Radiofrequency Thoracic Sympathectomy for Palmar Hyperhidrosis - Romero, Flávio Ramalho [UNESP]; Cataneo, Daniele Cristina [UNESP]; Cataneo, Antonio José Maria [UNESP] (Elsevier, 2018)
The impact of upper thoracic percutaneous sympathectomy with radiofrequency on the quality of life (QOL) of patients with palmar hyperhidrosis was evaluated. Thirty-six patients with palmar hyperhidrosis were selected for a prospective observational study. Treatment consisted of percutaneous radiofrequency thoracic sympathectomy of T3 and T4 ganglions in all cases. QOL questionnaires were applied preoperatively, on the 1st postoperative (PO) day, and on the 30th, 90th, 180th, and 360th PO days. Furthermore, compensatory hyperhidrosis (HDSSc) scale measures were used simultaneously, in order to evaluate the rate and frequency of this side effect. The QOL questionnaire evaluation showed preoperative values of 83.94 ± 4.74 (meaning poor quality of life), decreasing to 24.61 ± 2.86 on the 1st PO day, 25.14 ± 3.12 on the 30th PO day, 31.28 ± 4.42 on the 90th PO day, 32.97 ± 4.54 on the 180th PO day, and 33.94 ± 4.6 on the 360th PO day (all postoperative results with values below 35 were considered optimal). Compensatory hyperhidrosis (HDSSc) scale values were 1.14 ± 0.35 on the 1st PO day, 1.42 ± 0.55 on the 30th PO day, 1.83 ± 0.85 on the 90th PO day, 1.92 ± 0.91 on the 180th PO day, and 1.92 ± 0.91 on the 360th PO day (meaning that hyperhidrosis was mainly unnoticed). Patients’ subjective satisfaction was considered very good and the majority of patients would recommend the treatment procedure. Percutaneous radiofrequency thoracic sympathectomy had a positive impact on the quality of life of patients with palmar hyperhidrosis, compared to the surgical treatment, with a low rate and intensity of HDSSc and without other complications.
Keywords: Compensatory hyperhidrosis; compensatory hyperhidrosis; Dermatology Life Quality Index; DLQI; Glossary of abbreviations: HDSSc; Hyperhidrosis Disease Severity Scale; Palmar hyperhidrosis; Percutaneous sympathectomy; QOL; quality of life; Radiofrequency